Equine herpesvirus myeloencephalopathy - TGW, Teodoro; FS, Mendonça; J, Asin (Brazilian Journal of Veterinary Pathology, 2023)
A euthanized, 14-year-old, Warmblood gelding that had participated in an equine show was presented for necropsy anddiagnostic workup to the San Bernardino laboratory of the California Animal Health and Food Safety Laboratory System. Theanimal had a 4-day history of mildly swollen limbs and hyperthermia, and developed neurologic signs shortly before euthanasi